2018
DOI: 10.1111/ajt.14981
|View full text |Cite
|
Sign up to set email alerts
|

Graft-versus-host disease of the central nervous system after liver transplantation: A rare complication

Abstract: Graft-versus-host disease (GVHD) of the central nervous system (CNS) following solid organ transplantation is a rare but serious complication and has been previously reported after bone marrow transplantation. GVHD after liver transplantation is a rare entity with a high mortality rate. We report the case of a patient who developed GVHD and subsequently had seizures and altered mental status after deceased donor liver transplantation. The diagnosis of GVHD of the CNS was established by short tandem repeat loci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The median follow-up period after LT was 84 days (IQR, 45–180), 2 , 4 , 11 13 , 15 19 , 21 , 22 , 24 , 26 31 , 33 , 35 , 37 39 , 43 , 44 , 46 61 , 64 , 66 – 72 , 74 , 75 , 77 – 80 , 82 , 83 , 85 , 86 , 88 97 , 99 108 , 111 120 , 122 , 124 129 whereas the median follow-up period following GvHD onset was 32 days (IQR, 19–67). 11 13 , 15 , 17 19 , 22 24 , 26 31 , 33 , 36 39 , 42 , 44 , 46 49 , 51 , 53 58 , 60 , 61 , 64 , 66 , 67 , 69 72 , 74 , 75 , 77 – 83 , ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The median follow-up period after LT was 84 days (IQR, 45–180), 2 , 4 , 11 13 , 15 19 , 21 , 22 , 24 , 26 31 , 33 , 35 , 37 39 , 43 , 44 , 46 61 , 64 , 66 – 72 , 74 , 75 , 77 – 80 , 82 , 83 , 85 , 86 , 88 97 , 99 108 , 111 120 , 122 , 124 129 whereas the median follow-up period following GvHD onset was 32 days (IQR, 19–67). 11 13 , 15 , 17 19 , 22 24 , 26 31 , 33 , 36 39 , 42 , 44 , 46 49 , 51 , 53 58 , 60 , 61 , 64 , 66 , 67 , 69 72 , 74 , 75 , 77 – 83 , ...…”
Section: Resultsmentioning
confidence: 99%
“…Few data refer to the therapeutic regime of GvHD following SOT in the current literature. Furthermore, the majority of cases have been published as case reports; 2 4 , 16 – 18 , 22 , 25 , 28 , 30 , 31 , 34 38 , 42 46 , 48 54 , 56 , 58 , 60 , 61 , 65 , 67 , 69 77 , 80 – 90 , 92 , 95 103 , 105 – 109 , 111 120 , 122 128 , 130 , 132 134 , 138 141 thus, obtaining an overview of this sophisticated topic is aggravated. Treatment options for SOT-GvHD are also controversial as there is limited evidence given the scarcity and unaltered high mortality of cases, foreclosing a conclusive evidence-based therapy recommendation.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, organs such as kidney, CNS, and lungs may be involved in patients experiencing aGVHD after allogeneic hematopoietic stem cell transplantation. Pahari et al [ 18 ] reported the first case of CNS-GVHD following LT. Subsequently, seizures and altered mental status were recorded, and the patient died of sepsis and multiorgan failure.…”
Section: Discussionmentioning
confidence: 99%
“…, donor lymphocyte chimerism in recipient tissues (peripheral blood, skin, GI tract, bone marrow, or buccal mucosa), especially with a high proportion of CD8+ T cells, persists 3-4 wk after LT and thus is associated with the eventual development of GVHD. Recently, chimerism analysis assessed the donor DNA using fluorescent in situ hybridization and the short tandem repeat (STR) loci to quantitate the donor’s contribution to any of the nucleated cell populations in the skin, peripheral blood, GI mucosa, and/or bone marrow, and cerebrospinal fluid[ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical manifestations include encephalopathy, seizures, and focal neurologic deficits such as hemiparesis. [62][63][64][65][66]…”
Section: Cns Graft Versus Host Diseasementioning
confidence: 99%